2024
DOI: 10.1111/jar.13181
|View full text |Cite
|
Sign up to set email alerts
|

From assistive to inclusive? A systematic review of the uses and effects of technology to support people with pervasive support needs

Lotte Piekema,
Annet ten Brug,
Aly Waninge
et al.

Abstract: BackgroundAlthough particular technologies can enhance the quality of life (QoL) of people with profound intellectual and multiple disabilities (we use the term pervasive support needs), their objectives and outcomes are understudied. A systematic literature review was therefore conducted to explore this topic.MethodA search of four databases yielded 64 studies. Data were extracted on their general characteristics, methods and sample characteristics as well as the technology types, QoL domains and application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 126 publications
(240 reference statements)
0
1
0
Order By: Relevance
“…Consequently, further research is warranted to discern potential disparities in their viewpoints compared to those of other healthcare professionals and parents. Another limitation includes the formulation of the central prompt as it did not retrieve statements on hindering or promoting factors regarding the utilisation of the support strategies, considering that previous research suggest that some support strategies identified in the current study have specific limitations in practice (Kruithof et al, 2024;Nicholson et al, 2023;Piekema et al, 2024). Furthermore, this study utilised the Self-determination Theory (SDT) to guide participants' responses to the central prompt.…”
Section: Limitationsmentioning
confidence: 99%
“…Consequently, further research is warranted to discern potential disparities in their viewpoints compared to those of other healthcare professionals and parents. Another limitation includes the formulation of the central prompt as it did not retrieve statements on hindering or promoting factors regarding the utilisation of the support strategies, considering that previous research suggest that some support strategies identified in the current study have specific limitations in practice (Kruithof et al, 2024;Nicholson et al, 2023;Piekema et al, 2024). Furthermore, this study utilised the Self-determination Theory (SDT) to guide participants' responses to the central prompt.…”
Section: Limitationsmentioning
confidence: 99%